2016
DOI: 10.1002/ardp.201600197
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of 4‐Anilinothieno[2,3‐d]pyrimidine‐Based Compounds as Dual EGFR/HER‐2 Inhibitors

Abstract: Dual inhibition of the epidermal growth factor receptor (EGFR) and the human epidermal growth factor receptor 2 (HER-2) is an attractive cancer therapeutic approach. In this study, new series of 4-anilinothieno[2,3-d]pyrimidines were designed, synthesized, and tested as dual EGFR/HER-2 kinase inhibitors. Five compounds (8a, 8b, 8e-g) demonstrated low to submicromolar inhibition of both kinases with IC values of 1.2, 0.6, 0.3, 0.2, 0.4 μM and 8.2, 3.4, 1.3, 0.5, 2.7 μM for the EGFR and HER-2, respectively. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The progress of reaction was monitored by TLC, after completion of disappearance of starting materials, cooled the reaction mixture to ambient temperature and the resulting solids were filtered and dried under vacuum. The obtained crude solid was further purified by recrystallization by ethanol to afford desired compound- 1 ( 9.76 g, yield: 80.1% ) as a yellow crystal [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The progress of reaction was monitored by TLC, after completion of disappearance of starting materials, cooled the reaction mixture to ambient temperature and the resulting solids were filtered and dried under vacuum. The obtained crude solid was further purified by recrystallization by ethanol to afford desired compound- 1 ( 9.76 g, yield: 80.1% ) as a yellow crystal [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some of these compounds are summarised in Figure 2. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Interestingly, it has been noted that 4-amino substituents, whether aryl/aryl alkyl or urea, play a crucial role in binding to cancer proteins. These findings, particularly regarding the 6-membered ring fused theino [2,3-d]pyridines and their medicinal properties, prompted us to develop a more efficient delivery system for new 4-amino substituted 5,6,7,8tetrahydrobenzo [4,5]thieno [2,3-d]pyrimidines.…”
Section: Synthesismentioning
confidence: 99%
“…In 2016, Abd El Hadi et al reported the synthesis of two series of 4-anilinothieno[2,3-d] pyrimidines which were assessed as dual EGFR/HER2 kinase inhibitors (Fig. 8) [87]. Series A contains compounds that were less potent inhibitors for EGFR/HER2 kinase than Series B.…”
Section: Thienopyrimidine Derivatives As Egfr/ Her2 Dual Inhibitorsmentioning
confidence: 99%